KARAKTERISTIK TEGANGAN TEMBUS DAN ARUS BOCOR ISOLATOR PITA TEGANGAN RENDAH - , INDRA MAULANA; , Prof. Dr. Ir. T.Haryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Electricity is a basic human need that can not be separated from human life, it can be seen from the household sector, industry, and other sectors that need electricity. At the start of the power system generation, transmission lines, distribution channels, until it gets to the customer, the electricity distribution requires the correct treatment for the system is still safe to consume. The issue of isolation is one of the most important issues in high voltage engineering. Insulation is a material that can be electrically separating two or more adjacent conductors so that there is no leakage currents or in the case of high gradient, does not cause sparks (flashover). One important part of high-voltage equipment is part of the insulation that require insulation that has electrical properties like breakdown strength, high resistivity, low losses. Besides insulating materials are also required to have good mechanical properties among which have resilience and tensile compressive force that is able to withstand the mechanical and electrical disturbance due to high operating on the high voltage. Therefore, it is required a study to determine the breakdown voltage characteristics and leakage current at the various layers of insulation in particular various types of insulation tape on the market. From the results of this test can be seen the magnitude of the voltage that is able to hold and it can be seen that the leakage current also occurs in the insulating tape.